DIP1 modulates stem cell homeostasis in Drosophila through regulation of sisR-1. - Wong, J.T.; Akhbar, F.; Ng, A.Y.E.; Tay, M.L.; Loi, G.J.E.; Pek, J.W. (Nature communications, 2017)
Stable intronic sequence RNAs (sisRNAs) are by-products of splicing and regulate gene expression. How sisRNAs are regulated is unclear. Here we report that a double-stranded RNA binding protein, Disco-interacting protein 1 (DIP1) regulates sisRNAs in Drosophila. DIP1 negatively regulates the abundance of sisR-1 and INE-1 sisRNAs. Fine-tuning of sisR-1 by DIP1 is important to maintain female germline stem cell homeostasis by modulating germline stem cell differentiation and niche adhesion. Drosophila DIP1 localizes to a nuclear body (satellite body) and associates with the fourth chromosome, which contains a very high density of INE-1 transposable element sequences that are processed into sisRNAs. DIP1 presumably acts outside the satellite bodies to regulate sisR-1, which is not on the fourth chromosome. Thus, our study identifies DIP1 as a sisRNA regulatory protein that controls germline stem cell self-renewal in Drosophila.Stable intronic sequence RNAs (sisRNAs) are by-products of splicing from introns with roles in embryonic development in Drosophila. Here, the authors show that the RNA binding protein DIP1 regulates sisRNAs in Drosophila, which is necessary for germline stem cell homeostasis.